PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TALKING STICK UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN KESETIMBANGAN KIMIA DI KELAS XI MIA SMA NEGERI 1 UJUNGBATU - Annisa Rahayu Rahayu; Asmadi M noer Noer; Roza Linda Linda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The aim of this research is to improve student achievement on the subject  chemical equilibrium in class XI Senior High School (SMAN) 1 Ujungbatu trough the applying model cooperative learning Talking Stick . This research was used Randomized control Group Pretest-Posttest design. The data are research was conducted from September 2014 to June 2015. The population of the research are all of student in XI Senior High School (SMAN) 1 Ujungbatu which consists of 5 classes. Samples of this research have two classes there are class XI MIA.4 and XI MIA.5 were randomly selected. Class XI MIA.5 applied model cooperative learning Talking Stick as experiment class and  XI MIA.4  as control class. The data analysis technique used homogeneity test is by assessing homogeneous variances of samples, and hypothesis test (t-test) is by assessing comparison of learning achievement between class. Based on analysis hypothesis test with   d f = 61 (α= 0,05) data obtained arithmetic > table is 2,9 > 1,67. It showed that model cooperative learning Talking Stick can improve student achievement on the subject chemical equilibrium class XI Senior High School (SMAN) 1Ujungbatu. Based on normalized gain (N-gain) category increased in experiment class by student achievement was categorized in high (0,776) category, while control class categorized medium(0,682) category.Key Word : Cooperative Learning, Talking Stick, Chemical Equilibrium